Czech drama during the protectorate - Janousek, Pavel (Bohemica Olomucensia, 2019)
This text is a draft of a chapter from the upcoming publication History of Czech literature in Protectorate of Bohemia and Moravia, prepared by the collective of authors under the leading of Pavel Janousek a funded by the grant project GA CR 18-14478S. Shortened and modified versions of already published studies "Alegorie o moru, hrichu, spolecnosti, dusi, trestu a obeti" (in Pavel Janousek: ... a dalsi studie, Academia 2018) a "Hry o pozaru" are part of this text, too. The author of the subchapter about Frantisek Zavrel is Eduard Burget.
Keywords: poetics of drama; allegorical drama; historical drama